Long Over-Due Process: Proposing a New Standard for Pretrial Detainees' Length of Confinement Claims - Huennekens, Kendall (2022)
Prolonged pretrial detention poses one of the greatest unchecked threats to due process in the United States. The Supreme Court has never announced the proper analysis to adjudicate detainees’ allegations of prolonged detention pending trial (for criminal detainees) or removal (for noncitizens in immigration detention centers). Because the Court has continually ducked this constitutional question, detainees and courts alike lack guidance regarding how to vindicate this fundamental liberty interest. This Note identifies the inconsistencies in the Court’s due process jurisprudence generally, as well as the dangers intrinsic to collapsing the standards used to evaluate pretrial detainees’ claims under the Due Process Clause and prisoners’ claims under the Eighth Amendment. In the wake of the Court’s holding in Kingsley v. Hendrickson, this Note argues that the Court should expand an objective due process analysis to detainees’ overdetention claims in place of the subjective analysis derived from the Eighth Amendment. This Note further argues that freedom from overdetention is a fundamental right protected by substantive due process, and it proposes a framework with graduated levels of scrutiny to be applied to pretrial criminal detainees’ and noncitizens’ overdetention claims